BIMBINGAN KELOMPOK BERBASIS ONLINE PADA SISWA MA AL-MUKHTARIYAH MANDE YANG MEMILIKI PERILAKU ASERTIF RENDAH - Febby Rahmawati; Heris Hendriana; Tita Rosita (IKIP Siliwangi, 2021)
This study is aimed at knowing the description of group guidance services on low assertive behavior in students. Assertive behavior is very influential on the social life of students if students have low assertive behavior then they must be treated immediately in the form online-based group guidance services. This research was conducted at MA Al-Mukhtariyah Mande. The subject were 3 students of class XI who had low assertive behavior as a results of the rekommendations of guidance and counseling teachers at school. In ths study, the approach used is a qualitative approach with a descriptive method. The data collection techniques in this study are interviews, observation and documentation. The results showed that students after being given online-based group guidance services got a good response and changes in behavior that were shown in accordance with the aspect shown in assertive behavior, such as being able to express feelings comportably, act according to their own interests, defend themselves, and not deny the right of others.Keywords: group guidance, assertive